Comparison of NiOx thin film deposited by spin-coating or thermal evaporation for application as a hole transport layer of perovskite solar cells. Issue 71 (8th December 2020) - Kim, Su-Kyung; Seok, Hae-Jun; Kim, Do-Hyung; Choi, Dong-Hyeok; Nam, Seung-Ju; Kim, Suk-Cheol; Kim, Han-Ki
Abstract : We compared nickel oxide (NiO x ) deposited by thermal evaporation and that deposited by the spin-coating process, for use in the hole transport layers of inverted planar perovskite solar cells (PSCs). Abstract : We compared nickel oxide (NiO x ) deposited by thermal evaporation and that deposited by the spin-coating process, for use in the hole transport layers of inverted planar perovskite solar cells (PSCs). Spin-coating deposition for NiO x HTL has been widely used, owing to its simplicity, low cost, and high efficiency. However, the spin-coating process has a technical limit to depositing a large-area uniformly. In contrast, thermal evaporation fabrication has a low price and is able to produce uniform and reproducible thin film. Hence, the chemical states, energy band alignment, surface morphologies, and microstructures of NiO x deposited by spin coating and thermal evaporation were analyzed. The PSC with NiO x HTL deposited by thermal evaporation showed a higher power conversion efficiency of 16.64% with open circuit voltage 1.07 V, short circuit current density of 20.68 mA cm −2, and a fill factor of 75.51% compared to that of PSC with spin-coated NiO x . We confirmed that thermal evaporation can deposit NiO x to give a better performance as a HTL with higher reproducibility than spin-coating.